Kocuria soli sp. nov., an actinobacterium isolated from soil. Issue 7 (15th May 2019) - Tuo, Li; Li, Fei-Na; Bao, Yu-Xin; Yan, Xiao-Rui; Sun, Cheng-Hang
Abstract : A Gram-stain-positive, aerobic, coccoid-shaped, non-spore-forming actinobacterial strain, designated M5W7-7 T, was isolated from a hot spring soil sample collected from Anshan, Liaoning province, PR China. Phylogenetic analysis based on 16S rRNA gene sequences revealed that strain M5W7-7 T clustered closely with species of the genus Kocuria, and showed the highest sequence similarity of 97.1 % to Kocuria subflava YIM 13062 T . Strain M5W7-7 T grew at 10–37 °C (optimum, 37 °C), pH6.0–11.0 (pH 6.0–7.0) and in the presence of 0–7 % (w/v) NaCl (0 %). Substrate mycelia and aerial mycelia were not formed, and diffusible pigments were not observed on any media tested. Strain M5W7-7 T contained MK-6(H2 ) and MK-7(H2 ) as the dominant menaquinones. The polar lipid profile of strain M5W7-7 T contained diphosphatidylglycerol, phosphatidylglycerol, two unidentified glycolipids, an unidentified phospholipid and an unidentified lipid. The predominant whole-cell sugars were galactose and glucose. The predominant fatty acid was anteiso-C15 : 0 . The DNA G + C content of strain M5W7-7 T was 67.0 mol%. On the basis of phylogenetic relationships, phenotypic characterization and chemotaxonomic analyses, strain M5W7-7 T represents a novel species of the genus Kocuria, for which the name Kocuria soli sp. nov. is proposed. The type strain is M5W7-7 T (=KCTC 49195 T =CGMCC 1.13744 T ).